Edukasi Skrining HIV Mandiri: Intervensi Informasi Untuk Populasi Kunci - Gusni Rahma; Yulia; Welly; Febry Handiny (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2025)
HIV AIDS is still a public health problem in Indonesia, with the number of cases reaching 543,100. Key populations such as sex workers, injecting drug users, men who have sex with men (MSM) and transgenders contribute a relatively high proportion of cases. Lack of knowledge and low awareness of the importance of early detection are the main obstacles in prevention efforts. This community service aims to increase knowledge and attitudes and encourage independent HIV screening behavior in key populations through education. The activity methods include counseling and the distribution of leaflets. The activity was carried out in January 2025 in Padang, involving 25 participants from key populations. The stages of this community service include preparation, implementation, and evaluation. The evaluation results of this activity were an increase in knowledge from 55% to 78% and a positive attitude from 50% to 75%, so it can be concluded that community-based education can increase understanding and attitudes about early detection of HIV among key populations.